Risk Factors and Long‐Term Outcomes of Tricuspid Regurgitation After Transcatheter Closure of Pediatric Perimembranous Ventricular Septal Defects - Diandong Jiang; Yingchun Yi; Lijian Zhao; Jing Wang; Yan Wang; Jianli Lv; Xiaofei Yang; Jianjun Zhang; Bo Han; Fen Li (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Transcatheter closure of perimembranous ventricular septal defects in children is a highly effective procedure, but it can result in tricuspid regurgitation (TR). The associated risk factors and long‐term outcomes of TR following the procedure are not well understood. METHODS AND RESULTS This retrospective study included 1343 pediatric patients (age, 4.41±2.56 years) who underwent successful transcatheter perimembranous ventricular septal defect closure between 2002 and 2022, with a median follow‐up of 78 (range, 12–244) months. TR was evaluated using echocardiography, and multivariate logistic regression was performed to identify independent risk factors of postprocedural TR. Postprocedural TR occurred in 12.1% of patients, including 143 new‐onset cases and 20 with progressed preexisting TR. The majority of cases (86.5%) were mild, while 20 were moderate, and 2 were severe requiring surgical intervention. Most TR cases (84%) developed within 24 hours after the procedure. A higher right disc diameter‐to‐body weight ratio was identified as an independent risk factor of TR (odds ratio, 2.816 [95% CI, 1.315–6.032]). During follow‐up, 71.8% of TR cases improved or resolved, though moderate TR persisted in 7 cases, and 1 progressed to severe TR requiring surgery 2 years after the procedure. Conclusions TR following perimembranous ventricular septal defect closure is common but typically mild and often resolves over time. A larger right disc diameter relative to body weight significantly increases the risk of TR, emphasizing the importance of careful device sizing, particularly in lighter patients. Long‐term follow‐up is crucial to detect potential late progression of TR.